Analisis Literatur: Aspek-Aspek Positif dan Keterbatasan Pembelajaran STEM - Angjelina, Putri; Riandi, Riandi (Universitas Sarjanawiyata Tamansiswa, 2023)
This research examines related to STEM learning. This study discusses the positive aspects and limitations of STEM learning. This study uses Literature Review or literature review with a model of synthesizing Scopus indexed scientific articles, totaling 15 articles. The results of the literature review show that there are positive aspects in STEM learning, namely creating cohesive learning, improving science process skills, influencing student achievement, motivating students in learning, increasing student creativity, increasing student career interest. and learning becomes more meaningful because it can develop problem solving skills, creative and analytical thinking, and collaboration. Then the limitations in STEM learning are the lack of division of tasks, scheduling, lack of dexterity, disputes. In addition, the use of technological equipment requires special time before lessons. Especially in the product design process, trying to provide sufficient space and order in the classroom for group work. The topics used are only suitable for STEM learning topics related to complex problems.